Pengembangan Kemampuan Fisik Motorik Melalui Permainan Tradisional Bagi Anak Usia Dini - Hasanah, Uswatun (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2016)
Retracted Following a rigorous and careful concerns and consideration in the review of the article published in Al-Athfal: Jurnal Pendidikan Anak entitled: “Pengembangan Kemampuan Fisik Motorik Melalui Permainan Tradisional Bagi Anak Usia Dini” Vol. 2, No. 1, pp. 115-134, Juni 2016, Permenlink/DOI: - . This paper has been found to violate the principles of Al-Athfal: Jurnal Pendidikan Anak Publication and has been retracted. The editor has found that the paper has been published in Jurnal Pendidikan Anak, Vol. 5, No. 1, pp. 717-733, 2016, DOI: https://doi.org/10.21831/jpa.v5i1.12368 The document and its content have been removed Al-Athfal: Jurnal Pendidikan Anak, and reasonable effort should be made to remove all references to this article. Permalink: http://ejournal.uin-suka.ac.id/tarbiyah/index.php/alathfal/article/view/1232